Ownership Structure in Cameroon’s Private Limited Companies and the Quality of their Financial Reporting: the mediating role of the audit quality - VANETISSA BOUBA , Esdras; TONYE BATEES FILS , PATOU (Revue Internationale des Sciences de Gestion, 2024)
Financial reporting is an important factor affecting investor decisions since it contributes rapidly and efficiently to the pricing and valuation performance and functions of stock markets. The most important source of information about companies in developing countries is their financial statements. Investors demand to rely on companies’ financial statement information when making their decisions. Through identifying these characteristics, investors will be able to make the best choice and will have access to information that will boost the financial statements’ credibility The purpose of this research is to investigate the relationship between the ownership structure in Cameroon Private Limited Companies (Ltds) and their financial statements. To evaluate the strength of this link, the audit quality has been introduced as mediating factor. A sample of 205 staff working either at the managing director’s office or at the financial department from 86 Cameroon Ltds were questioned by means of electronic questionnaires. Our results indicate that the audit quality partially mediates the relationship between ownership structure and quality of financial reporting.